Detection of alkylating agents by the analysis of amino acid residues in hemoglobin and urine 1. The in vivo and in vitro effects of ethyl methanesulfonate, methyl methanesulfonate, hycanthone methanesulfonate, and naltrexone - Truong, Lan; Ward, Jonathan B.; Legator, Marvin S. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1978)
The effect of alkylating agents on the amino acid composition of rat and human hemoglobin has been examined. Because the amino acid compositions of these proteins are well established, the changes in the molar ratios of specific amino acids could be monitored in purified hemoglobin samples. Ratios of histidine, which is readily attacked by alkylating agents, to proline, which is not, were consistent in hemoglobin purified from untreated blood samples from 14 rats and 25 human subjects. Treatment of hemoglobin in vitro or in vivo with methyl methanesulfonate, ethyl methanesulfonate, or hycanthone methanesulfonate resulted in a loss of histidine residues relative to proline or phenylalanine. The decrease in histidine content increased with treatment dose and time and reached a maximum at about 15% of total histidine. Treatment of rats with methyl methanesulfonate or hycanthone methanesulfonate resulted in increased urinary excretion of methyl histidines.